ANALISIS KEMAMPUAN MENULIS NARASI MELALUI PEMANFAATAN POJOK BACA DALAM PEMBELAJARAN KELAS V DI SD NEGERI PEKUNDEN - Rizqi Shofiah, Nurlaili; Asri Untari, Mei; Listyarini, Ikha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Education in the current global era is important for the welfare of society. There are four aspects that influence an individual’s reading interest, namely reading activity, awareness of reading, reading frequency, and the quality of reading materials. Writing is an important activity in learning after reading. In brief, a narrative is a story that presents a sequence of events involving conflict. The role of the reading corner is important and provides many benefits. This study aims to examine students’ narrative writing skills through the use of the reading corner, how the reading corner is utilized in the learning process, and the factors that support and hinder its use in fifth grade at SD Negeri Pekunden Semarang. This research employs a descriptive qualitative method. Based on the overall results obtained from data collection techniques, it can be concluded that the utilization of the reading corner has a positive impact on students’ narrative writing skills.